ANALISIS RISIKO PADA PRODUK BERAKAD BAGI HASIL PERBANKAN SYARIAH INDONESIA - SE, M.Si, Ak, Yohani (Majalah Neraca, 2012)
This research has a purpose to analyze the deferences of risk âsharing product Â at indonesian islamic banking. The statistic method used to test on the research hypothesis is Independent t test. To analyzed the data using secondary data. Â Sample of this research consist two bank, Sharia Mandiri Banking and Muammalat Banking. Its listed at www,muamalatbank.com and www.syariah mandiri.co.id from Â 2002 â 2011 with times series.Â The result of these study Â with level of significance 5% uji independent t test show that (1) risk financing between of Muamalat Banking and Syariah Mandiri Banking statistically itâsnot different significantly. (2) risk of return on mudaraba financing and capital at Muamalat Banking Â lower than Mandiri Syariah Banking. Its mean that the risk financing Â for sharia product is not influenced by the history and the old age of Islamic banks, but the mudharba return on Muamalat Banking more stable so risk of return smaller.Keyword : Sharia Product, Financing risk, Return Risk